2017
DOI: 10.1111/nmo.13230
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic gastroparesis is associated with specific transcriptional changes in the gastric muscularis externa

Abstract: Our findings suggest that idiopathic gastroparesis is associated with altered smooth muscle cell contractile protein expression and loss of PDGFRα cells without a significant change in ICCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 49 publications
2
34
1
Order By: Relevance
“…In summary, we have shown that expression of mRNA encoding FOXF1 and FOXF2 is decreased in human subjects with gastroparesis and that loss of both these proteins from adult smooth muscle in mice is sufficient to impair liquid gastric emptying. These findings together with our previous studies showing FOXF regulation of SRF/myocardin transcriptional complexes and altered transcriptional activity of contractile protein genes in the stomach of patients with gastroparesis suggest that SRF containing transcriptional complexes may play a central role in pathological changes that lead to gastroparesis.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In summary, we have shown that expression of mRNA encoding FOXF1 and FOXF2 is decreased in human subjects with gastroparesis and that loss of both these proteins from adult smooth muscle in mice is sufficient to impair liquid gastric emptying. These findings together with our previous studies showing FOXF regulation of SRF/myocardin transcriptional complexes and altered transcriptional activity of contractile protein genes in the stomach of patients with gastroparesis suggest that SRF containing transcriptional complexes may play a central role in pathological changes that lead to gastroparesis.…”
Section: Discussionsupporting
confidence: 78%
“…None of these 14 controls subjects had diabetes (normal HbA1c <1 month prior to surgery; Figure A). The clinical description of these patients was described previously . The second group included 11 patients undergoing bariatric weight loss surgery that had diabetes (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations